Culture, politics, and national identity in Wales, 1832-1886 - Cragoe, Matthew (Oxford University Press, 2004)
This detailed, scholarly exploration of Welsh political culture in the 19th century offers a new interpretation of the rise of nationalism. The author shows how the focus of legitimate power in the community shifted from the aristocracy to the urban middle classes.